Learning to 'Be/Live' in Kathmandu City: Kirat Migrants' Transformation - Rai, Indra Mani (Journal of Education and Research, 2017)
This paper, based on auto/ethnographic inquiry, explores how particular urbanised Kirats (internal migrant ethnic community members in Kathmandu city from the East of Nepal) learn to live in Kathmandu city. The paper argues that the formal education in Nepal, guided by Western modern worldviews as hegemony, is promoting imported instrumental knowledge and skills, which are impractical and less relevant in the job market, particularly in the city context. The paper further argues that the work based learning support them to transform to become particular urban professionals. However, those Kirats are made forced-learners in urban structures for their adaptation in a new context. Such forced-learning is subjugating indigenous knowledge inherited to them from their ancestors and accumulated in their village life.